(untitled) (Journal of Global Accounting, 2024)
Despite the external auditors’ reports for listed companies, inadequate quality reports still exist, leading to business collapse and great concern for the investors and other stakeholders. In lieu of this, this study examined the effect of environmental sustainability reporting, social sustainability reporting and economic sustainability reporting on the financial reporting quality of listed customer goods firms in Nigeria. Ex-post facto research design was employed for the study and data were obtained from secondary sources through the annual reports of sampled firms for the period of 2012 to 2022. Twenty-one (21) consumer goods firms listed on the Nigerian Exchange Group as of 31st December 2022 constitute the population of the study. The entire twenty-one (21) consumer goods firms listed on the Nigerian Exchange Group were sampled using census sampling technique. The independent variable, sustainability reporting, was measured with environmental sustainability reporting, social sustainability reporting and economic sustainability reporting while the dependent variable, financial reporting quality, was measured using Jones Discretionary Accrual Score. Data were analyzed using descriptive statistics and panel corrected standard errors regression. The findings revealed that environmental sustainability reporting has a positive and insignificant effect on the financial reporting quality of listed consumer goods firms in Nigeria. Social sustainability reporting has a negative and insignificant effect on the financial reporting quality of the sampled firms. Economic sustainability reporting has a negative but significant effect on the financial reporting quality of the sampled firms. The study concluded that economic and social dimension of sustainability which includes concerns about labour practices, human rights, and relationships with the communities in which a firm operates, are highly significant factors that negatively influence the financial reporting quality, especially for the consumer goods firms in Nigeria. The study recommends that relevant stakeholders should look into the regulatory provision of accounting guidelines regarding environmental reporting to improve on it due to its benefit and positive influence on financial reporting quality.